Natural ventilation around open round floors with pilotis in high-rise residential buildings in tropical areas: harmonization of modern and traditional housing in tropical areas - Sapian, Abdul Razak; Abdul Majid, Noor Hanita; Hokoi, Shuichi (Mukogawa Women's University Press, 2012)

(untitled)
In this paper, we propose using pilotis in tropical urban areas to harmonize the benefits of modern and traditional housing. The thermal and airflow conditions of a building that has pilotis are compared with those of a building that does not have pilotis, and we examine how the thermal and airflow conditions near the ground floor of the high-rise building can be improved by constructing the pilotis. Furthermore, the notion that natural ventilation on the upper floors is not seriously worsened by constructing pilotis is also examined by computational fluid dynamics CFD)analysis.